Strengthening the Capacity of Nasyiatul Aisyiyah Cadres through Eco-Enzyme-Based Soap and Shampoo Product Innovation - Rahmi Amir; Amri Amri; Tahir Tahir; Mutmainnah Mutmainnah; Z.A. Farham Farham (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2026)
Background: The suboptimal management of household organic waste remains an environmental issue as well as an economic opportunity at the community level. Nasyiatul Aisyiyah cadres, as young women, have strategic potential in developing environmentally based entrepreneurship, but they still need enhanced knowledge and practical skills. This activity contributed to increasing public awareness of household organic waste management, strengthening women’s economic empowerment, and reinforcing the role of Nasyiatul Aisyiyah cadres as agents of change in building a sustainable community economy. Method: This community service program was implemented through the Muhammadiyah National Research Community Service Grant Batch IX 2025 using a participatory training and mentoring approach. The activities included the introduction of eco-enzyme concepts, hands-on practice in producing eco-enzymes from household organic waste, soap and shampoo formulation, and basic entrepreneurship strengthening. Results: The results showed a 40% improvement in participants' understanding of household organic waste management, based on pre-test and post-test evaluations. Additionally, 85% of participants successfully formulated and packaged eco-enzyme-based soap and shampoo products. Conclusion: This activity successfully achieved its objective of strengthening the capacity of Nasyiatul Aisyiyah cadres. Eco-enzyme-based product innovation has the potential to become an integrative community service model by linking environmental preservation with community entrepreneurship empowerment.